2020
DOI: 10.3390/antiox9090874
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Oxidative Stress as Potential Therapeutic Approach for Normal Tension Glaucoma

Abstract: Glaucoma is a neurodegenerative disease of the eye, which involves degeneration of retinal ganglion cells (RGCs): the output neurons of the retina to the brain, which with their axons comprise the optic nerve. Recent studies have shown the possible involvement of oxidative stress in the pathogenesis of glaucoma, especially in the subtype of normal tension glaucoma. Basic experiments utilizing rodent and primate models of glaucoma revealed that antioxidants protect RGCs under various pathological conditions inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 81 publications
0
39
0
Order By: Relevance
“…Indeed, although IOP elevation is known as one of the most recurrent risk factors for glaucoma ( Nickells et al, 2012 ) and is the main target of pharmaceutical treatments ( Stein et al, 2021 ), often it could manifest only at late stages of the disease or may not occur, as in the case of normotensive glaucoma ( Weinreb et al, 2014 ). Similar to diabetic retinopathy, oxidative stress is likely to represent a major trigger also for glaucoma ( Domènech and Marfany, 2020 ; Garcia-Medina et al, 2020 ; Harada et al, 2020 ; Wang et al, 2020 ), and LG, which does not have any effect on the rise of IOP characteristic of D2 mice, is likely to exert its protective effect thanks to its powerful antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although IOP elevation is known as one of the most recurrent risk factors for glaucoma ( Nickells et al, 2012 ) and is the main target of pharmaceutical treatments ( Stein et al, 2021 ), often it could manifest only at late stages of the disease or may not occur, as in the case of normotensive glaucoma ( Weinreb et al, 2014 ). Similar to diabetic retinopathy, oxidative stress is likely to represent a major trigger also for glaucoma ( Domènech and Marfany, 2020 ; Garcia-Medina et al, 2020 ; Harada et al, 2020 ; Wang et al, 2020 ), and LG, which does not have any effect on the rise of IOP characteristic of D2 mice, is likely to exert its protective effect thanks to its powerful antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…This model shows glaucomatous phenotypes such as RGC loss, optic nerve atrophy, and visual impairment while maintaining normal IOP [ 3 , 4 ]. Although the early onset of RGC degeneration in GLAST +/- mice is atypical compared with human glaucoma, it may be an advantage to carry out basic experiments in a short span of time [ [3] , [4] , [5] , [6] , [7] , [8] ]. We first examined the effects of lighting environment in GLAST +/- mice and found that RGC degeneration started before 3 weeks old in the Dark/Dark condition.…”
Section: Discussionmentioning
confidence: 99%
“…Since glutathione has a strong anti-oxidative effect, both glutamate neurotoxicity and oxidative stress may be involved in RGC degeneration in GLAST-deficient mice. On the other hand, intraocular pressure (IOP) in GLAST-deficient mice was not increased compared with wild-type mice, thus these mice may be utilized as a model of normal tension glaucoma [ [5] , [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%
“…17 In vivo experiments using animal models of glaucoma (based on apoptosis signal regulating kinase 1, valproic acid, N-acetylcysteine, spermidine, and coenzyme Q10) have showed that administering antioxidants had a neuroprotective effect. 18 These research suggest that antioxidants are a potential candidate for glaucoma therapy.…”
Section: Introductionmentioning
confidence: 98%